Pneumonia impact on the flow and the outcome at patients with seasonal influenza - Cvetanovska, Marija; Milenkovikj, Zvonko; Grozdanovski, Krsto; Demiri, Ilir; Spasovska, Katerina; Cvetanovski, Vlatko (European Respiratory Society, 2020)
Abstract Seasonal influenza complications are the cause of development of severe clinical picture as well as death. The most common are the respiratory ones, and the leading one that stands out is the secondary bacterial pneumonia. The aim of this study is determining the pneumonia impact on the severity of the clinical picture as well as the outcome for the patients with influenza. The research is prospectively compared in groups, carried out at University Clinic for Infectious Diseases during a 3-year period. 122 adult patients with clinical and laboratory confirmed influenza have been analyzed. Based on the severity of the clinical picture, patients were divided into two groups, a severe (n=87) and a mild (n=35) form of the disease. During the study demographic, general data, clinical symptoms and signs as well as complications have been recorded. Out of 122 patients with influenza, there were registered complications at 108 (88.52%), with significant appearance in the group with severe influenza 93.1% vs 77.14% (p=0.012). The most common one in percentage is pneumonia 98(80.33%) which also significantly influenced the severity of the disease (p=0.002). Complications such as ABI 8(6.56%), ARDS 7(5.74%), sepsis 5(4.1%), DIC 4(3.28%), and otitis 2(1.64%) have been registered only in the group with severe influenza. At 5(4.1%) patients acute meningoencephalitis has been registered, gastroenterocolitis at 3(2.46%), an hepatic damage at 14(11.47%) of the patients. Pneumonia as the most common complication for patients with severe influenza has significant impact on the clinical flow ant the outcome of the disease.